Hubungan Pengetahuan Ibu Hamil Trimester I dengan Kejadian Anemia di Wilayah UPTD Puskesmas Cibugel - Nonoh Nonoh; Nurhasanah Nurhasanah; Erni Ratna Suminar (Jurnal Ventilator, 2023)
Based on data from the World Health Organization, the prevalence of anemia in pregnant women worldwide has decreased by 4.5%. In Sumedang Regency in 2022 the number of pregnant women is 17,877 and there are 491 pregnant women who experience anemia, including the UPTD area of the Cibugel Inpatient Health Center. The aim of the study was to determine the relationship between the knowledge of first trimester pregnant women and the incidence of anemia in the UPTD area of the Cibugel Inpatient Health Center, Sumedang Regency, in 2023. This research was a quantitative study with a cross sectional survey approach. The population of this study were all pregnant women in the working area of the UPTD Puskesmas Cibugel, totaling 167 people. The sampling technique used accidential sampling to produce 39 research samples. The results showed that most of the respondents had sufficient knowledge of 24 people. Most of the respondents did not experience the incidence of anemia in pregnancy as many as 26 people and there was a relationship between knowledge and the incidence of anemia in pregnancy with a value of p = 0.001 <? = 0.05 so it can be concluded that most of the respondents had sufficient knowledge and did not experience anemia in pregnancy and there was a relationship between respondents' knowledge of the incidence of anemia in pregnancy in the UPTD area of the Cibugel Inpatient Health Center, Sumedang Regency in 2023. It is recommended that pregnant women take an active role in fulfilling information from various media, especially about anemia..